Association of betel nut chewing with exercise performance in a military male cohort: the CHIEF study. Issue 6 (16th July 2018) - Tsai, Kun-Zhe; Lin, J-W; Lin, F; Su, F-Y; Li, Y-H; Lin, Y-P; Lin, Y-K; Han, C-L; Hsieh, C-B; Lin, G-M
Abstract : Introduction: Betel nut chewing may cause obesity, neurohormonal activation and inflammation, possibly impairing exercise performances. Methods: We examined the cross-sectional association in 4388 military male adults aged 18–50 years from the cardiorespiratory fitness in armed forces study in Taiwan between 2013 and 2014. The status of betel nut chewing was classified as current and former/never based on each participant's response to a questionnaire. Physical fitness was evaluated by three basic exercise tests including 3000 m running, 2 min sit-ups and 2 min push-ups. Multiple logistic regression for the best 10% and the worst 10% performers in each exercise, and linear regression were used to determine the relationship. Results: There were 564 current chewers and 3824 non-current chewers for the analysis. The linear regression shows that current betel nut chewing was positively correlated with 3000 m running duration (r=0.37, p=0.042) after adjusting for age, service specialty, body mass index, exercise frequency and alcohol intake. In addition, the logistic regression shows that as compared with non-current chewers, current chewers had lower odds of being the top 10% performers in 2 min push-ups and higher odds of being the bottom 10% performers in 2 min sit-ups (ORs and 95% CIs: 0.71 (0.50 to 0.99) and 1.32 (1.00 to 1.75), respectively). However, the associations between betel nut chewing and physical fitness were all insignificant after further adjusting for current smoking. Conclusions: Our findings suggest that the impairment of physical fitness associated with betel nut chewing of military young men might be mainly mediated or moderated by the coexisted cigarette smoking.